SMILE CORRECTION WITH GINGIVAL HYPERPLASIA AFTER ORTHODONTIC TREATMENT. A LITERATURE REVIEW. - Segundo, Cícero Francismary Almeida Alves Feitoza (2024)
The present study aims to present ways of treating and correcting a smile with gingival hyperplasia after orthodontic treatment. An extensive literature review was carried out to identify relevant studies regarding the proposal of the present study. Electronic databases, such as: Scientific Electronic Library (Scielo), Google Scholar, Pubmed, were consulted to obtain published articles. Gingival hyperplasia is common during orthodontic treatment, due to poor oral hygiene, as orthodontic accessories do not cause damage to the gingival tissues. With this, it is concluded that basic periodontal therapy associated with good oral hygiene proved to be essential for achieving successful treatment of gingival hyperplasia. Periodontal gingivectomy and gingivoplasty surgeries, when well indicated, promote good aesthetics and harmony of the smile, contributing positively to the oral health and quality of life of patients.